Improving Students’ Achievement in Energy Resources Theme by Using Edusainsnopoly in Grade IV at SDN 3 Karang Tengah (Universitas Negeri Semarang, 2019)
The aim of this study is to improve the students achievement in energy resources theme by using Edusainsnopoly in grade IV of elementary school. The type of study is a Classroom Action Research using 2 cycles. The result of analyzing data and reflection in every cycles show the improvement of students’ achievement by using energy resources theme is higher than that of student’s who using contextual learning in the classroom. The achievement percentage target indicators is 75%, but in cycle 1 the percentage is about 72%. Since it have not fulfilled yet the achievement target indicators, so it continues to cycle II. In cycle II, the percentage of the achievement target indicators increases into 84%, which mean that there are about 12% of increasing. According to the result above it shows that the use of edusainsnopoly media can improve the students achievement in energy source, theme in grade IV of elementary school.